Ibm – Penguatan Nilai Tambah Ekonomi Masyarakat Desa Melalui Pengembangan Produk Pangan Olahan Berbasis Kentang (Potatoes) Di Dusun Klandungan, Desa Landungsari, Kecamatan Dau Kabupaten Malang - Agung Prasetyo Nugroho Wicaksono; Aris Soelistyo (Ethos: Jurnal Penelitian dan Pengabdian kepada Masyarakat, 2022)
Efforts to increase community income to increase the ability to process potato-based food, potato donuts food to become a potential independent entrepreneur, and increase the family stage will also impact the development of diversification of nutritious food products based on local wisdom. This community service program serves to develop the potential of the people of Landungsari Village, Dau District, Malang Regency in developing potato-based processed food products into nutritious “Potato Donuts” and is expected to increase the income of the village community.This community service activity was carried out by providing hands-on training in making potato-based processed food products into potato donuts. The output of this activity is in the form of SOPs for making potato donuts and standard national publication journals. The service method is carried out with an extension approach and direct practice on the spot.